Lack of Conserved miRNA Deregulation in HPV-Induced Squamous Cell Carcinomas - Nunvar, Jaroslav; Pagacova, Lucie; Vojtechova, Zuzana; Azevedo, Nayara Trevisan Doimo de; Smahelova, Jana; Salakova, Martina; Tachezy, Ruth (Biomolecules, 2021)
Squamous cell carcinomas (SCCs) in the anogenital and head and neck regions are associated with high-risk types of human papillomaviruses (HR-HPV). Deregulation of miRNA expression is an important contributor to carcinogenesis. This study aimed to pinpoint commonly and uniquely deregulated miRNAs in cervical, anal, vulvar, and tonsillar tumors of viral or non-viral etiology, searching for a common set of deregulated miRNAs linked to HPV-induced carcinogenesis. RNA was extracted from tumors and nonmalignant tissues from the same locations. The miRNA expression level was determined by next-generation sequencing. Differential expression of miRNAs was calculated, and the patterns of miRNA deregulation were compared between tumors. The total of deregulated miRNAs varied between tumors of different locations by two orders of magnitude, ranging from 1 to 282. The deregulated miRNA pool was largely tumor-specific. In tumors of the same location, a low proportion of miRNAs were exclusively deregulated and no deregulated miRNA was shared by all four types of HPV-positive tumors. The most significant overlap of deregulated miRNAs was found between tumors which differed in location and HPV status (HPV-positive cervical tumors vs. HPV-negative vulvar tumors). Our results imply that HPV infection does not elicit a conserved miRNA deregulation in SCCs.
Keywords: vysoce účinné nukleotidové sekvenování; Male; Papillomavirus Infections; regulace genové exprese u nádorů; orgánová specificita; Urogenital Neoplasms; urogenitální nádory; Humans; microRNA; Carcinoma, Squamous Cell; Sequence Analysis, RNA; mužské pohlaví; Female; human papillomavirus; MicroRNAs; Anus Neoplasms; tonzilární nádory; squamous cell carcinoma; Tonsillar Neoplasms; nádory anu; ženské pohlaví; spinocelulární karcinom; sekvenční analýza RNA; Gene Expression Regulation, Neoplastic; Organ Specificity; mikro RNA; lidé; infekce papilomavirem; High-Throughput Nucleotide Sequencing